ADSORPTIVE REMOVAL OF TANNIC ACID BY ACTIVATED CARBON FROM AQUEOUS SOLUTION - Singh, Shubhjeet (My University, 2013)
Tannic Acid (TA) is a specific commercial form of tannin, a type of polyphenol. Commercial TA has the formula C76H52O46. TA is a constituent of natural organic matter and occurs naturally from the breakdown of plant biomass. Therefore, it is found in surface and ground water naturally. Also, it is found in industrial wastewater discharged from coir and cork process, plant medicine, paper, and leather industries. A carcinogenic disinfection by-product such as trihalomethane can form in presence of TA during chlorination process for drinking water production. In addition as a water soluble polyphenolic compound, tannic acid has toxicity for aquatic organisms such as algae, fish and invertebrates. In this study, adsorptive removal of TA from aqueous solution on to commercial activated carbon (ACC) was evaluated. pH study showed that highest TA removal efficiency of 67.5% and 66.02% were obtained at pHi = 2 and 3, respectively. There is no significant differences in the TA removal at pHi = 2 and 3, therefore, pHi = 3 was chosen as optimum pHi (pHi-opt) to save the acid used for pH adjustment. Adsorbent dosage study showed that an increase in ACC dosage resulted in an increase in TA removal up to a certain value and thereafter the removal efficiency remained almost constant. An increase in the removal with the increase in mad can be attributed to greater surface area and the availability of more adsorption sites. Very minute increase in TA removal was found for mad ≥ 15 g/l f. Pseudo-first-order and pseudo-second-order kinetic models used to examine their validity with the experimental kinetic adsorption data and pseudo second-order kinetic model with non-linear regression best fits the adsorption kinetics. Isothermal experiments were performed at 291, 301 and 311 K with C0 values of 50, 100 and200 mg/l at pHi-opt and mad-opt of ACC. Various isotherms such as Freundlich, Langmuir and Redlich-Peterson (R-P) were used to represent the adsorption equilibrium data. The TA adsorption onto ACC was found to increase with an increase in T. Therefore, it can be concluded that TA adsorption onto ACC is an endothermic process. It was found that any of the isotherms can be used for isotherm modeling. But , it may be concluded that R-P isotherm generally best-fits the equilibrium adsorption of TA onto ACC at all temperatures. Very poor desorption of TA was observed with the NaOH and ethanol and are nearly same. Acetone showed maximum desorption of TA from spent adsorbents amongst chemical desorption. Thermal desorption of TA from ACC showed maximum desorption amongst chemical and thermal desorption methods.
M. Tech. Thesis
Keywords: Tannic Acid, Adsorption, Activated Carbon; Isotherms